PENGARUH KONFLIK INTERPERSONAL DAN BEBAN KERJA TERHADAP STRES KERJA PADA KANTOR SEKRETARIAT DAERAH KOTA DENPASAR - Aristantya Dewi, I Gusti Ayu Agung Desy; Wibawa, I Made Artha (E-Jurnal Manajemen, 2016)
The purpose of this study was to determine the effect of interpersonal conflicts and the workload of the employees simultaneously work stress, interpersonal conflict to determine the effect of work stress on employees, to determine the effect of workload on employee stress of the Regional Secretariat of Denpasar. Research was conducted on the staff of the Regional Secretariat of Denpasar. Samples used as many as 205 employees consisting of 11 parts of the Regional Secretariat of Denpasar. Data were collected by interviews, surveys and questionnaires. Data analysis technique used is multiple linear regression analysis and using the F test and t test. The results showed that interpersonal conflicts and significant positive effect on job stress of employees of the Regional Secretariat of Denpasar and workload positive and significant effect of the stress of employees working in the Office of the Regional Secretariat of Denpasar. Workloads have greater influence on the stress of work of the Regional Secretariat of Denpasar.
Keywords: Interpersonal Conflict, Workload, Work Stress